Agile Leadership: The Key to Unlocking the Effects of Work-Life Balance and Career Development on Employee Retention in Construction Company - Made Sasanti, Ni; Pintor Siolemba Patiro, Shine; Maharani, Anita (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to examine the influence of work-life balance career development on turnover intention with agile leadership as a moderator. Design/methodology/approach: The approach used in this research is quantitative. The sample used in this research was construction company “X” employees, totaling 159 respondents. Research data was obtained by filling out a questionnaire and analyzed using SEM analysis techniques with the help of the SEM PLS program. Research Findings: The results of this research show that (1) Work-life balance has a negative and significant effect on turnover intention; the higher the work-life balance, the lower the turnover intention, and vice versa, the lower the work-life balance, the higher the turnover intention; (2) Career development has a negative and significant effect on turnover intention, the higher the career development, the lower the turnover intention, and vice versa, the lower the career development, the higher the turnover intention; (3) Agile leadership does not moderate the influence of work-life balance on turnover intention. Whether in companies with good or bad agile leadership, there is the same influence between work-life balance and turnover intention. (4) Agile leadership does not moderate the influence of career development on turnover intention. Whether in companies with good or bad agile leadership, career development and turnover intention have the same influence. Theoretical Contribution/Originality: These findings provide valuable insights for organizational leaders and human resource professionals, empowering them to implement strategies that enhance work-life balance, foster career development, and mitigate turnover intention.